Bimetallic Gold(I) Complexes with Ethynyl‐Helicene and Bis‐Phosphole Ligands: Understanding the Role of Aurophilic Interactions in their Chiroptical Properties. Issue 17 (23rd March 2016) - El Sayed Moussa, Mehdi; Chen, Hui; Wang, Zuoyong; Srebro‐Hooper, Monika; Vanthuyne, Nicolas; Chevance, Soizic; Roussel, Christian; Williams, J. A. Gareth; Autschbach, Jochen; Réau, Régis; Duan, Zheng; Lescop, Christophe; et al.
Abstract: Monometallic gold(I)‐alkynyl‐helicene complexes (1 a, b ) and bimetallic gold(I)‐alkynyl‐helicene architectures featuring the presence (2 a, b ) or absence (3 a, b ) of aurophilic intramolecular interactions were prepared by using different types of phosphole ligands (mono‐phospholeL1 or bis‐phospholesL2, 3 ). The influence of the Au I d 10 metal center(s) on the electronic, photophysical, and chiroptical properties of these unprecedented phosphole‐gold(I)‐alkynyl‐helicene complexes was examined. Experimental and theoretical results highlight the importance of ligand‐to‐ligand‐type charge transfers and the strong effect of the presence or absence of Au I –Au I interactions in2 a, b . Abstract : Golden interactions : Monometallic and bimetallic gold(I)‐alkynyl‐helicene complexes featuring the presence or absence of aurophilic intramolecular interactions have been prepared by using different types of phosphole ligands (mono‐phosphole or bis‐phospholes). The influence of the Au I d 10 metal center(s) on the electronic, photophysical, and chiroptical properties in those novel systems has been examined (see scheme).